2021
DOI: 10.1213/ane.0000000000005810
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Alleviates Gut-Vascular Barrier Damage and Distant Hepatic Injury Following Intestinal Ischemia/Reperfusion Injury in Mice

Abstract: BACKGROUND: Intestinal ischemia/reperfusion (I/R) challenge often results in gut barrier dysfunction and induces distant organ injury. Dexmedetomidine has been shown to protect intestinal epithelial barrier against I/R attack. The present study aims to investigate the degree to which intestinal I/R attack will contribute to gut-vascular barrier (GVB) damage, and to examine the ability of dexmedetomidine to minimize GVB and liver injuries in mice. METHODS: In vivo, intestinal ischemic challenge was induced in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…β-catenin is essential for reducing the vascular permeability and bacterial penetration (Spadoni, Zagato et al, 2015;Mouries, Brescia et al, 2019;Zhang, Chang et al, 2022). Several studies demonstrated that upregualtion of β-catenin could improve GVB in pathologic conditions (Birdsey, Shah et al, 2015;Mouries, Brescia et al, 2019;Zhang, Chang et al, 2022). When we knocked down β-catenin in endothelial monolayer, the increased TER, tight and adhesin junction proteins and decreased permeability across HUVEC monolayers conferred by terlipressin sharply changed (Figure 6).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…β-catenin is essential for reducing the vascular permeability and bacterial penetration (Spadoni, Zagato et al, 2015;Mouries, Brescia et al, 2019;Zhang, Chang et al, 2022). Several studies demonstrated that upregualtion of β-catenin could improve GVB in pathologic conditions (Birdsey, Shah et al, 2015;Mouries, Brescia et al, 2019;Zhang, Chang et al, 2022). When we knocked down β-catenin in endothelial monolayer, the increased TER, tight and adhesin junction proteins and decreased permeability across HUVEC monolayers conferred by terlipressin sharply changed (Figure 6).…”
Section: Discussionmentioning
confidence: 95%
“…The sample size analysis was performed based on our literature (Zhang, Chang et al, 2022) and the Power and Sample Size online software (http://powerandsamplesize. com/Calculators/).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for intestinal injury mechanisms, dexmedetomidine may inhibit p38MAPK, and TLR4/MyD88/NF-κB signaling pathways and activate Jak/STAT signaling pathways, attenuating intestinal injury ( 74 76 ). Reportedly, dexmedetomidine pretreatment alleviates intestinal vascular barrier injury and is clarified to attenuate distal liver injury ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…DEX has been reported to be a potential drug for the prevention and treatment of intestinal I/R injury ( 7 , 9 , 16 , 18 , 19 ). Our results elaborated that the protection from DEX in mice with intestinal I/R injury evidenced with an inhibition of inflammation, ER stress-dependent apoptosis, and oxidative stress in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%